Effects of inulin and xanthan gum on the physical, digestibility, sensory and nutritional properties of sugar-free green banana flour biscuit - Yi Lin Lau; Chee Kiong Siew; Jumardi Rosland; Ai Ling Ho; Yanty Noorzianna Abdul Manaf; Jahurul Haque Akanda; Pei-Teng Chan; Jau-Shya Lee (Acta Scientiarum Polonorum Technologia Alimentaria, 2025)
Sweet biscuits are one of the most popular snacks in the world, but the long-term consumption of sucrose-containing high-glycemic index (GI) biscuits can contribute to obesity, type 2 diabetes and car- Dio vascular disease. The present work explored the possibility of producing a sugar-free biscuit using green Saba banana flour, which has been reported to have a lower GI than wheat flour. Material and methods. A 2 × 3 factorial design was used to investigate the effects of xanthan gum (0% and 1%) and inulin (0%, 25% and 50%) on a sugar-free biscuit made of Saba green banana flour. The quality of the biscuits was analyzed in terms of water activity, geometric indices, texture, in vitro digestibility and Esti- mated GI. A sensory evaluation was carried out to determine the changes caused by hydrocolloid modulation and to assess the acceptance of the sugar-free biscuits. Results. The hydrocolloids notably affected the quality of the sugar-free biscuits, with greater positive effects observed as the levels of both ingredients increased. Comparatively, inulin had a more pronounced influence than xanthan gum in modifying the properties of the biscuits. The sugar-free biscuit with the highest sensory evaluation score (1% xanthan gum and 50% inulin) contained more dietary fiber and had a lower GI and glycemic load (GL) than the sugar-containing control. Conclusions. This study demonstrates the feasibility of producing a healthier, sugar-free biscuit with an im- proved starch digestion profile using inulin and xanthan gum. However, further improvements to the texture of the sugar-free biscuit are required. Future studies could investigate the relationship between dough Rheo- logy, biscuit structure and sensory perceptions to uncover more insights for product improvement.